Concurrent Afatinib and Whole-Brain Radiotherapy in Exon 19-del-EGFR Mutant Lung Adenocarcinoma: A Case Report and Mini Review of the Literature - Eze, Chukwuka; Hegemann, Nina-Sophie; Roengvoraphoj, Olarn; Dantes, Maurice; Manapov, Farkhad (Frontiers in Oncology, 2017)
Leptomeningeal metastases are found in approximately 3.8% of NSCLC cases with an increased incidence in adenocarcinoma and approximately a third of patients will present with concomitant brain metastases. We report the case of a 50-year-old male patient with stage IV exon 19-del-EGFR mutant lung adenocarcinoma who progressed on second-generation TKI-Therapy with manifestation of symptomatic simultaneous diffuse brain and leptomeningeal metastases. Whole brain radiotherapy with concurrent afatinib resulted in an almost complete regression of neurological symptoms as well as good, durable radiological response. Furthermore, treatment was well-tolerated with no relevant adverse effects.